Infrared functional imaging applied to Raynaud's phenomenon. - Merla, A. (IEEE Engineering in medicine and biology magazine)
Presents an approach that allows simultaneous assessment of thermal properties of multiple fingers on both hands. It is a novel approach to the estimation of Raynaud's phenomenon based on infrared functional imaging assessments. Q, which represents the total amount of stored heat by the finger during the rewarming processes and is evaluated by means of the area under the time-temperature curve, seems to be particularly effective in order to describe the thermal recovery capabilities of the finger, also in terms of thermal efficiency. Q clearly highlights the difference between primary Raynaud's phenomenon and secondary scleroderma patients, and between patients and normal as well, and provides useful information about the abnormalities of their thermoregulatory finger properties.